Comparative differences in job preferences among doctors in different levels of public hospitals in Henan, China: a discrete choice experiment - Wang, Jingjing; Lv, Hui; Qin, Qin; Ren, Wenjie; Mohd Shariff, Noorsuzana (Frontiers in Psychology, 2025)
BackgroundDoctor turnover is a significant challenge faced by hospitals worldwide, particularly in public hospitals in China. By understanding how job attributes influence job preferences among doctors, effective and targeted policies can be designed to attract doctors to key positions or organizations, providing insights for evidence-based workforce interventions.ObjectivesThe aim of our study is to examine the difference of job preferences of doctors in different hospitals levels using DCE.MethodsA discrete choice experiment was applied in the public hospital in China. A total of 920 eligible doctors from primary, secondary, and tertiary public hospital in China participated in this study. A mixed logit model was applied to assess job preferences among doctors in public hospital in China.ResultsDoctors in primary hospitals preferred job offers with 30% salary increase over the unchanged (OR = 8.906, p < 0.001). Similar trends were observed in secondary and tertiary hospitals (OR = 4.785, p < 0.001; OR = 5.56, p < 0.001). Doctors from all hospital levels (primary, secondary, and tertiary) preferred sufficient opportunities of professional development (OR = 1.43, p = 0.032; OR = 1.47, p = 0.008; OR = 1.44, p < 0.001). A 20% increase in workload was generally less favored in all hospital levels (OR = 0.63, p = 0.015; OR = 0.45, p < 0.001; OR = 0.42, p < 0.001). Environmental support was only preferred in tertiary hospitals (OR = 1.46, p < 0.001). Monthly salary was the top priority for doctors across all hospital levels, followed by work atmosphere. Employee care came third in primary and secondary hospitals, while opportunities of professional development ranked the third in tertiary hospitals. Environmental support from hospital was the least prioritized factor in both secondary hospitals, while workload was the least important in primary and tertiary hospitals.ConclusionDoctors preferred job offers with salary increases across all hospital levels. Professional development opportunities were prioritized universally, while 20% increase in workload was generally least favored. Environmental support was most important in tertiary hospitals. Monthly salary and work atmosphere were top priorities across all hospital levels, with employee care ranking third in primary and secondary hospitals. Workload and environmental support were the least prioritized, varying by hospital level.